SUMBER OTORITAS PELAKSANAAN SUPERVISI - Metti Fathimah; Taufiq Khoirin; Miftahurrohman (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Educational supervision is an essential instrument for improving the quality of teaching and the professional competence of teachers. For supervision to be effective, it requires a strong, legitimate, and accountable foundation of authority. This paper examines four sources of authority in educational supervision—juridical, administrative, scientific, and moral—and their significance in establishing a professional, objective, and developmental supervisory practice. Through a comprehensive review of literature, including national educational regulations, modern supervision theories, and recent research findings, this study highlights that the legitimacy of supervision does not rely solely on formal positions, but also on academic competence, moral integrity, and the supervisor’s ability to apply a humanistic approach. The findings emphasize that integrating all four sources of authority is crucial so that supervision is not perceived merely as bureaucratic control, but rather as a professional mentoring process that supports continuous improvement in teaching quality. This study provides a comprehensive insight for supervisors, school principals, and policymakers in strengthening the foundations of educational supervision in practice.